STRATEGIC DECISION MAKING FOR BUSINESS DEVELOPMENT AND PROFIT OPTIMIZATION USING THE ANALYTICAL HIERARCHY PROCESS: THE CASE OF KLINIK PRATAMA SINDANG SARI - Reza Yudha Fadillah; Meditya Wasesa (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Health is important for the well-being of the community, and basic clinics are important places for people in Indonesia to get health treatment. Klinik Pratama Sindang Sari has been committed to providing great service since it opened in 1997. In 2024, it received "Paripurna" (excellent) accreditation. Even though the clinic knows this, it still has trouble being financially stable, mostly because it relies heavily on BPJS capitation, which makes up 80% of its income. Rising costs of doing business and not enough variety make it even harder for it to earn profit. This study looks into ways for Klinik Pratama Sindang Sari to build its business in a smart way that will help its finances. The study uses Value-Focused Thinking (VFT), the Analytic Hierarchy Process (AHP), Stakeholder Analysis, Focus Group Discussions, and the Kepner-Tregoe Problem Analysis to find and rank alternative service innovations. The Analytic Hierarchy Process (AHP) is very important for judging four proposed strategies: Vaccine Service Implementation; Dental Aesthetic Care; Corporate Health Screening Cooperation; and BPJS Capitation Optimization. It does this by looking at factors like cost, regulation, market demand, profit potential, and implementation challenges.